A comprehensive approach to developing L2 speaking competence - Robbie Lee Sabnani; Willy A. Renandya (Universitas Islam Malang, 2019)
Speaking is important to language learners. The ability to structure talk facilitates effective communication with fellow interlocutors. A strong spoken command positions them to participate actively in interactions with their teachers and peers to hone their academic mastery. This article presents a principled approach to improve the accuracy and fluency of learners’ utterances through the teaching speaking cycle (Goh & Burns, 2012). It comprises seven strategically sequenced stages to increase learners’ knowledge of language and discourse, enhance their core skills and heighten their awareness and use of communication strategies. Based on a methodological framework underpinned by cognitive, metacognitive and socio-affective domains, the model provides for rehearsal, task repetition and focused teaching to strengthen learners’ oral competence in a holistic manner. Complementing explicit instruction with contextualized practice develops learners’ introspective awareness of the elements and processes in speaking to gain greater autonomy over their progress.